2020
DOI: 10.5194/bg-2020-310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Limited Effect of Sub-Tropical Typhoons on Phytoplankton Dynamics

Abstract: Abstract. Typhoons are assumed to stimulate ocean primary production through the upward mixing of nutrients into the surface ocean, based largely on observations of increased surface chlorophyll concentrations following the passage of typhoons. This surface chlorophyll enhancement, seen on occasion by satellites, more often is undetected due to intense cloud coverage. Daily data from a BGC-Argo profiling float revealed the upper-ocean response to Typhoon Trami in the Northwest Pacific Ocean. Temperature and ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 63 publications
(89 reference statements)
0
4
1
Order By: Relevance
“…Still, as shown in Figure 1, the magnitude, location, and extremeness of TC-PBs vary depending on the satellite used. While it is suggested that some TC-PBs are the results of vertical homogenization of existing deep chlorophyll (Chai et al, 2020), we find that establishing a bloom threshold of 0.5 mg/m 3 rules out this process as generating the anomalous increases in Chl-a observed here. The complex interplay of upper-ocean stratification, wind-driven mixing, and rotationally driven Ekman suction is critical for understanding the response of the upper ocean and its ecosphere to TCs.…”
Section: Discussion + Conclusioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Still, as shown in Figure 1, the magnitude, location, and extremeness of TC-PBs vary depending on the satellite used. While it is suggested that some TC-PBs are the results of vertical homogenization of existing deep chlorophyll (Chai et al, 2020), we find that establishing a bloom threshold of 0.5 mg/m 3 rules out this process as generating the anomalous increases in Chl-a observed here. The complex interplay of upper-ocean stratification, wind-driven mixing, and rotationally driven Ekman suction is critical for understanding the response of the upper ocean and its ecosphere to TCs.…”
Section: Discussion + Conclusioncontrasting
confidence: 74%
“…The cold wake contained high concentrations of surface chlorophyll, in places estimated to exceed 15 mg/m 3 . High surface values are not likely to be the result of mixing of a deep Chl-a maximum as may occur in the Northwest Pacific or in weak observed blooms (Chai et al, 2020).…”
Section: Methods and Datamentioning
confidence: 96%
See 1 more Smart Citation
“…A noteworthy feature in this case is that the weaker TC Neoguri rapidly generated an obvious augment of phytoplankton biomass in the upper ocean. A category 5 typhoon Trami in late September 2018 with average translation speed of 6.1 m/s barely caused net increase of primary production in the upper ocean observed by BGC-Argo float 2902750, in spite of the stronger intensity and slower translation speed compared to Neoguri (Chai et al, 2021). Huang et al (2016) reported that TC Jangmi caused a weaker surface bloom owing to the thick ML induced by TC Sinlaku that passed earlier.…”
Section: Subsurface Chl-a Increase Induced By Two Sequential Tcsmentioning
confidence: 99%
“…The DCM is a ubiquitous phenomenon in worldwide oceans, formed by biological-chemicalphysical interaction. In the stratified open ocean, the vertical stratification below the ML suppresses the supply of nutrients from subsurface layer, generally leading to a DCM beneath the MLD and at the top of nutricline within the euphotic layer where there are adequate nutrients and light (Furuya, 1990;Cullen, 2015;Wang, 2020;Chai et al, 2021;Zhuang et al, 2021). On October 9, 2019, The DCM occurred at the depth of 59.9 m just above the nutricline.…”
Section: Subsurface Chl-a Increase Induced By Two Sequential Tcsmentioning
confidence: 99%